The Actualization of the Autonomous Norms of Village Regulations in Sekaran Lamongan Sub-District in Accommodating Village Needs in the Unitary State of the Republic of Indonesia - Adhitya Widya Kartika (Nusantara Science and Technology Proceedings)
Research on village regulations is important for the smooth functioning of village governments in carrying out their government functions. The legal norm, in this case, is regaling, which is an important village regulation to be compiled as a benchmark for the village government in carrying out its government functions. Village regulations are drawn up by village officials and villagers are expected to cover all the aspirations needed by the community and the government to develop the village concerned. However, if the lack of knowledge and socialization can cause things that are not expected to be achieved, then this research is needed to ensure that their implementation is following the norms in the law. This research was conducted with social-legal research with respondents who process secondary data and then conclude. The results of his research include that village regulation already exists in every village except that there are still many village regulations which are village regulations on annual village activities. For example about the village budget and village regulations related to village head reporting. Village regulations other than annual activities are only carried out by a few villages. Also, other provisions that can be stated in village regulations are still limited to verbal regulations or socialization, for example regarding the natural handling of village pests, one of which is by installing owl nests. This has not been stated in village regulations.